Intermediate- vs. Standard-Dose Prophylactic Anticoagulation in Patients With COVID-19 Admitted in Medical Ward: A Propensity Score-Matched Cohort Study - Smadja, David M.; Bonnet, Guillaume; Gendron, Nicolas; Weizman, Orianne; Khider, Lina; Trimaille, Antonin; Mirault, Tristan; Fauvel, Charles; Diehl, Jean-Luc; Mika, Delphine; Philippe, Aurelien; Pezel, Théo; et al. (Frontiers in Medicine, 2021)
Background: Microthrombosis and large vessels thrombosis are the main triggers of COVID-19 worsening. The optimal anticoagulant regimen in COVID-19 patients hospitalized in medical wards remains unknown. Objectives: To evaluate the effects of intermediate-dose vs standard-dose prophylactic anticoagulation among patients with COVID-19 hospitalized in medical wards. Methods and results: Using a large French multicentric retrospective study enrolling 2878 COVID-19 patients hospitalized in medical wards. After exclusion of patients who had an anticoagulation treatment before hospitalization, we generated a propensity-score-matched cohort of patients who were treated with intermediate-dose or standard-dose prophylactic anticoagulation between February 26 and April 20, 2020 (intermediate-dose, n = 261; standard-dose prophylactic anticoagulation, n = 763). The primary outcome of the study was in-hospital mortality; this occurred in 23 of 261 (8.8%) patients in the intermediate-dose group and 74 of 783 (9.4%) patients in the standard-dose prophylactic anticoagulation group (p = 0.85); while time to death was also the same in both treatment groups (11.5 and 11.6 days respectively, p = 0.17). We did not observed any difference regarding venous and arterial thrombotic events between intermediate dose and standard dose (respectively, venous thrombotic events: 2.3% vs 2.4%, p=0.99; arterial thrombotic events: 2.7% vs 1.2%, p=0.25).The 30-day Kaplan-Meier curves for in hospital mortality demonstrates no statistically significant difference in in-hospital mortality (HR: 0.99 (0.63–1.60); p = 0.99). Moreover, we found that no particular subgroup was associated with significant reduction of in-hospital mortality. Conclusion: Among COVID-19 patients hospitalized in medical wards, intermediate-dose prophylactic anticoagulation, compared with standard-dose prophylactic anticoagulation, did not result in a significant difference in in-hospital mortality.